Wider research applications of dynamic consent - Schuler Scott, A; Goldsmith, M; Teare, H (Springer, 2019)
As research processes change due to technological developments in how data is collected, stored and used, so must consent methods. Dynamic consent is an online mechanism allowing research participants to revisit consent decisions they have made about how their data is used. Emerging from bio-banking where research data is derived from biological samples, dynamic consent has been designed to address problems with participant engagement and oversight. Through discussion that emerged during a workshop run at the IFIP 2018 Summer School, this paper explores wider research problems could be addressed by dynamic consent. Emergent themes of research design, expectation management and trust suggested overarching research problems which could be addressed with a longer term view of how research data is used, even if that use is unknown at the point of collection. We posit that the existing model of dynamic consent offers a practical research approach outside of bio-banking.